2017
DOI: 10.1016/s0016-5085(17)30587-5
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Resonance Elastography vs Transient Elastography in Detection of Fibrosis and Noninvasive Measurement of Steatosis in Patients with Biopsy-Proven Nonalcoholic Fatty Liver Disease

Abstract: Background & Aims-Magnetic-resonance-imaging (MRI) techniques and ultrasound-based transient elastography (TE) can be used in noninvasive diagnosis of fibrosis and steatosis in patients with nonalcoholic fatty liver disease (NAFLD). We performed a prospective study to compare the performance of magnetic resonance elastography (MRE) vs TE for in diagnosis of fibrosis, and MRI-based proton density fat fraction (MRI-PDFF) analysis vs TE-based controlled attenuation parameter (CAP) for diagnosis of steatosis in pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
105
0
3

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 70 publications
(109 citation statements)
references
References 38 publications
1
105
0
3
Order By: Relevance
“…Although changes in liver stiffness by FibroScan were not significant, this may reflect the reduced precision and accuracy of FibroScan in obese patients. (44) This randomized trial assessed changes in liver fat content by MRI-PDFF and liver stiffness by MRE, along with liver biopsy assessments before and after treatment, with results assessed by central reviewers blinded to treatment assignments. Liver fibrosis on histology was assessed using a comprehensive set of parameters including NASH CRN fibrosis stage, quantitative digital morphometry, and a-SMA immunostaining before and after treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Although changes in liver stiffness by FibroScan were not significant, this may reflect the reduced precision and accuracy of FibroScan in obese patients. (44) This randomized trial assessed changes in liver fat content by MRI-PDFF and liver stiffness by MRE, along with liver biopsy assessments before and after treatment, with results assessed by central reviewers blinded to treatment assignments. Liver fibrosis on histology was assessed using a comprehensive set of parameters including NASH CRN fibrosis stage, quantitative digital morphometry, and a-SMA immunostaining before and after treatment.…”
Section: Discussionmentioning
confidence: 99%
“…VCTE is inexpensive and can be measured in the clinic but has inferior diagnostic performance in head-to-head comparison studies with MRE, particularly for lower stages of fibrosis and in the morbidly obese. (12)(13)(14) In contrast to liver biopsy, MRE evaluates a much larger volume of the total liver (~5%), is reproducible, (15) and has high interobserver agreement. (16) While cross-sectional studies have demonstrated that MRE has superior diagnostic performance in NAFLD, there are limited longitudinal data on the association between changes in MRE and liver fibrosis on paired liver biopsies.…”
Section: Clinical Utility Of An Increase In Magnetic Resonance Elastomentioning
confidence: 99%
“…(29)(30)(31)(32)(33) Liver stiffness was estimated using two-dimensional MRE, which is the most accurate biomarker for the quantitative assessment of liver stiffness as a surrogate for hepatic fibrosis. (13,14,34) A passive driver was fitted around the body over the liver and connected to an acoustic active driver that delivered continuous vibrations at 60 Hz to produce shear waves in the liver, which were processed to generate elastograms depicting liver stiffness. Four slices were assessed, and colocalized regions of interest were manually specified.…”
Section: Mrimentioning
confidence: 99%
“…(17) MRE has emerged as the most accurate tool to predict hepatic fibrosis, with an area under the receiver operating characteristic curve above 0.90 for all fibrosis stages (18,19) and higher accuracy than ultrasound-based elastography techniques (such as transient elastography or acoustic radiation force impulse elastography) for the detection of fibrosis in NAFLD. (20)(21)(22)(23) MRE has several advantages over ultrasound-based elastography, as it samples a much larger volume of the liver, is not affected by body mass index (24,25) or degree of steatosis, (14) is not operator-dependent, (26) has favorable test-retest repeatability, (26) and has a high success rate. (25,27) MRE estimates liver stiffness, which correlates to the amount of collagen deposition in the extracellular matrix, but liver stiffness is also influenced by other factors, such as inflammation, vascular congestion, and cholestasis.…”
mentioning
confidence: 99%